Pharmacological Modulators of Small GTPases of Rho Family in Neurodegenerative Diseases - Guiler, William; Koehler, Addison; Boykin, Christi; Lu, Qun (Frontiers in Cellular Neuroscience, 2021)
Classical Rho GTPases, including RhoA, Rac1, and Cdc42, are members of the Ras small GTPase superfamily and play essential roles in a variety of cellular functions. Rho GTPase signaling can be turned on and off by specific GEFs and GAPs, respectively. These features empower Rho GTPases and their upstream and downstream modulators as targets for scientific research and therapeutic intervention. Specifically, significant therapeutic potential exists for targeting Rho GTPases in neurodegenerative diseases due to their widespread cellular activity and alterations in neural tissues. This study will explore the roles of Rho GTPases in neurodegenerative diseases with focus on the applications of pharmacological modulators in recent discoveries. There have been exciting developments of small molecules, nonsteroidal anti-inflammatory drugs (NSAIDs), and natural products and toxins for each classical Rho GTPase category. A brief overview of each category followed by examples in their applications will be provided. The literature on their roles in various diseases (e.g. Alzheimer’s Disease, Parkinson’s Disease, Amyotrophic Lateral Sclerosis, Frontotemporal Dementia, and Multiple Sclerosis) highlights the unique and broad implications targeting Rho GTPases for potential therapeutic intervention. Clearly, there is increasing knowledge of therapeutic promise from the discovery of pharmacological modulators of Rho GTPases for managing and treating these conditions. The progress is also accompanied by the recognition of complex Rho GTPase modulation where targeting its signaling can improve some aspects of pathogenesis while exacerbating others in the same disease model. Future directions should emphasize the importance of elucidating how different Rho GTPases work in concert and how they produce such widespread yet different cellular responses during neurodegenerative disease progression.